The effect of adding boron in solidification microstructure of dilute iron-carbon alloy as assessed by phase-field modeling - Henrique Silva Furtado; Américo Tristão Bernardes; Romuel Figueiredo Machado; Carlos Antônio Silva (Materials Research, 2011)
Alloying element like boron, even in small addition, is well known to improve hardenability of steels. Its application can improve mechanical properties of steels and reduce alloying costs. Despite these benefits is not easy to cast boron steels, mainly in dynamical solidification process like continuous casting, due to their crack susceptibility1,2. The strategy of using Phase-Field simulation of the solidification process is based on its proved capacity of predicting realistic microstructure that emerge during solidification under conditions even far from equilibrium3-5. Base on this, some comparative simulations were performed using a three component dilute alloy in a two dimensional domain under unconstrained (isothermal) and constrained (directional) solidification. Simulation results suggested two fragile mechanisms: one related to a deep dendritic primary arms space and other due to the remelting of this region at low temperature. Both resulted mainly from the high boron segregation in interdendritic regions.